The production of social school democratic spaces for agency transformation - Liberali, Fernanda; Tanzi Neto, Adolfo (Calidoscópio, 2022)
This article discusses the production of social school democratic spaces for teachers’ and students’ agency transformation in a Latin American globalized context – Brazil, through their participation in an engaged multiliteracy project (Digitmed Program/Brazil), where some social, political, economic, and cultural issues are at the basis. In this program, there are all types of social exclusion such as age, gender, class, race, hearing differences; oppressions lived by educators and students; children and teenagers who work on streets as opposed by others who have a very limited perception of the surrounding reality; students involved with drugs, both as users and as dealers, students who consider suicide as an option, and other similar dramatic circumstances. The project involves a critical-collaborative intervention research (Magalhães, 2011) with private and public (municipal and state) schools, focusing on a university-school-community partnership for the joint construction of a school democratic social space for agency transformation. In this project, the concept of agency offers us basis to investigate the development of individuals in the critical transformation process of their social realities through engaged multiliteracy. Keywords: democratic space production; agency; globalized context, critical collaboration; engaged multiliteracy.